Laser Welding of Thin Sheet Magnesium Alloys - M., Ishak; Yamasaki, Kazuhiko; Maekawa, Katsuhiro (Intech Open Access Publisher, 2012)
Introduction: Magnesium and its alloys are active materials, and the oxide can easily form when they react with air and moisture (Czerwinski 2002). In addition, magnesium and its alloys are flammable and require strict safeguards during the manufacturing process. These disadvantages make the processing of magnesium alloys into finished products more challenging. These drawbacks cause defects such as cracks, oxide inclusion, burn-through and voids both during and after processing. In order to minimize these defects, most processing methods must be performed at a certain temperature, unlike aluminum alloys and steels, which may be finished by cold working. Defect reduction can be achieved by minimizing the complexity of parts and the number of components produced. Furthermore, improved design techniques and production processing can eliminate defects in the finished products.